Coronavirus: una pandemia hiperreal - Gadea, Carlos A.; Bayce, Rafael (El Colegio de México, 2020)
The global euphoria surrounding Coronavirus has forced us to rethink certain analytical links between uncertainty and fear, practical reality and hyperreal false certainty, as well as between science, politics, the media, common sense and public opinion. New social relationships have been established. It is possible to identify them in the form of a new social prophylaxis and a greater fear of contact between people, apprehensions associated with the fears already internalized since the time of AIDS and the experience of terrorism. Uncertainty and false certainties have gained even more ground despite the rise of the information society and the political measures undertaken for its eventual containment. Simmel’s pioneering sociology, Jakobs’s analysis of the “penal theory of the enemy,” hyperreality according to Baudrillard, and the notions of catastrophe and uncertainty support the following reflection on the implications and recent changes brought about by the global pandemic.